2018
DOI: 10.1177/1747021818808187
|View full text |Cite
|
Sign up to set email alerts
|

Decay of internal reference information in duration discrimination: Intertrial interval modulates the Type B effect

Abstract: Psychophysical evidence suggests that human perception of a stimulus is assimilated towards previous stimuli. The internal reference model (IRM) explains such assimilation through an internal reference (IR), which integrates past and present stimulus representations and thus might be conceived as a form of perceptual memory. In this study, we investigated whether the IR decays with time, as previously shown for perceptual memory representations in general. One specific prediction of IRM is higher discriminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…The second alternative is the internal reference model (Lapid, Ulrich, & Rammsayer, 2008; Bausenhart, Bratzke, & Ulrich, 2016; Bausenhart, Dyjas, & Ulrich, 2015; Dyjas & Ulrich, 2014; Dyjas, Bausenhart, & Ulrich, 2012, 2014; Ellinghaus, Gick, Ulrich, & Bausenhart, 2019). This generative model resembles the conventional framework for dual-presentation methods in that the decision variable is also computed as an unweighted difference and in that the decision space has a single boundary β in the comparative task (i.e., observers are never uncertain and never judge equality in this task) although the model replaces it with possibly asymmetric boundaries δ 1 and δ 2 for the equality task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second alternative is the internal reference model (Lapid, Ulrich, & Rammsayer, 2008; Bausenhart, Bratzke, & Ulrich, 2016; Bausenhart, Dyjas, & Ulrich, 2015; Dyjas & Ulrich, 2014; Dyjas, Bausenhart, & Ulrich, 2012, 2014; Ellinghaus, Gick, Ulrich, & Bausenhart, 2019). This generative model resembles the conventional framework for dual-presentation methods in that the decision variable is also computed as an unweighted difference and in that the decision space has a single boundary β in the comparative task (i.e., observers are never uncertain and never judge equality in this task) although the model replaces it with possibly asymmetric boundaries δ 1 and δ 2 for the equality task.…”
Section: Discussionmentioning
confidence: 99%
“…The second comment regards empirical tests supporting this model, beyond the empirical fact that Type A and Type B order effects are found in the data. Only in two studies (Bausenhart et al, 2015;Ellinghaus et al, 2019) model psychometric functions were fitted to the data in search for a functional description of performance via model parameters, but the most common way in which the model has been "tested" (e.g., Dyjas et al, 2012 is by fitting arbitrary and general-purpose psychometric functions in search for differences in slopes and locations estimated without the constraints that the model imposes. This was also true in the only study in which the use of alternative response formats with a within-subjects design would have allowed a true test of the prediction that differences in observed performance across presentation orders and response formats can be accounted for with identical estimates of (at least some of the) internal reference model parameters.…”
Section: Is the Indecision Model The Only Alternative Framework?mentioning
confidence: 99%
“…This effect should be reduced in the alternating condition if the variation of tone frequency leads to the formation of separate, stimulus-based internal references. Specifically, the effectively longer intertrial interval between two repetitions of the same stimulus frequency in the alternating compared to the constant presentation mode implies a stronger decay of each of the internal references and thus a reduced Type B effect (Ellinghaus et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In line with this assumption, it has been demonstrated that the temporal structure of an experimental task can modulate typical assimilation effects. For example, the Type B effect diminishes with increasing intertrial interval (Ellinghaus et al, 2019). This can be attributed to decay of the internal reference from previous trials with increasing delay between trials, which will result in a reduced influence (in terms of IRM, a smaller weighting factor) of prior relative to current stimulus information in the integration process.…”
Section: Memory Mixing As a Source Of The Central Tendency Sequential...mentioning
confidence: 99%
See 1 more Smart Citation